Consensus guidelines for the management of primary supra-tentorial intraventricular tumour for low- and middle-income countries - Hafiza Fatima Aziz; Saqib Kamran Bakhshi; Rabeet Tariq; Muhammad Waqas Saeed Baqai; Mohammad Hamza Bajwa; Kaynat Siddiqui; Zanib Javed; Ahsan Ali Khan; Muhammad Shakir; Pakistan Brain Tumour Consortium: (Authors list at the end of the supplement); et al. (Journal of the Pakistan Medical Association, 2024)
Almost any primary or metastatic brain tumour can manifest in intraventricular (IV) locations. These tumours may either originate within the ventricular system or extend into the IV space through growth. Such neoplasms represent a broad spectrum, with supratentorial IV tumours forming a heterogeneous group. This group includes primary ependymal tumours, central neurocytomas, choroid plexus tumours, and notably, meningiomas, as well as a variety of non-neoplastic, benign, glial, and metastatic lesions that can secondarily invade the IV compartment. Often presenting with nonspecific symptoms, these tumours can lead to delayed medical attention. The diversity in potential diagnoses, combined with their deep and complex locations, poses significant management challenges. This paper aims to delineate optimal management strategies, underscoring the importance of multidisciplinary care, especially in settings with limited resources, to effectively navigate the complexities associated with treating intraventricular brain tumours. Keywords: Meningeal neoplasms, meningioma, neurocytoma, choroid plexus, neoplasms, intraventricular tumour, supratentorial tumours.